(untitled) (Bangladesh Journal of Plant Taxonomy, 2015)
Rhododendron leigongshanense, a new species from Leishan County, Guizhou Province, China, is described and illustrated. The new species is close to R. magniflorun W.K. Hu and R. glanduliferum Franchet, but differs by having stipitatus glands on leaf abaxial surface, corolla trumpet-shaped with 7 lobes, 7.58.0 cm long, 810 cm in diameter and calyx 7- lobed. Bangladesh J. Plant Taxon. 22(2): 119-123, 2015 (December)